2020
DOI: 10.1016/j.omega.2019.102106
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of closed-loop supply chains under remanufacturing lead time variability

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  A closed-loop supply chain with reman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Their study showed that CLSCs tend to alleviate the bullwhip effect in comparison to forward supply chains. Likewise they found that the greater the return product rate the lesser the bullwhip effect, a finding also supported by Zhao et al (2018) and Dominguez et al (2019). Some scholars argue that remanufacturing can improve the reuse ratio and alleviate the bullwhip of closed-loop systems (Da et al 2008;Corum et al 2014).…”
Section: Bullwhip Effect On Reverse Logisticsmentioning
confidence: 86%
“…Their study showed that CLSCs tend to alleviate the bullwhip effect in comparison to forward supply chains. Likewise they found that the greater the return product rate the lesser the bullwhip effect, a finding also supported by Zhao et al (2018) and Dominguez et al (2019). Some scholars argue that remanufacturing can improve the reuse ratio and alleviate the bullwhip of closed-loop systems (Da et al 2008;Corum et al 2014).…”
Section: Bullwhip Effect On Reverse Logisticsmentioning
confidence: 86%
“…All these features are well suited for MAS modelling, allowing for analyzing the complexities of this new paradigm and studying the impact of the reverse flow of used products (and its associated processes to restore value) on the classic forward flow of new products. This is still an emerging area of research, and there are only a few studies using MAS [38,[94][95][96][97][98].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation has rapidly become an important methodological approach to theory development in the literature focused on strategy, organizations, and SCN management. It allows modelers to capture the dynamics of complex systems due to its capability of handling their dynamics and stochastic behavior, and enables managers to analyze and evaluate the effects of alternative configurations of the system, see, e.g., [36][37][38][39][40][41][42][43][44][45]. In particular, there has been a great interest in modeling SCNs as MAS in the past years [21,23], because there is a natural correspondence between the different actors in a SCN and agents in a MAS simulation model.…”
Section: Simulation and Masmentioning
confidence: 99%
See 1 more Smart Citation
“…These emerging models entail important environmental and economic opportunities, but also pose new challenges. Specifically, they raise additional layers of uncertainties, including those related to the variable nature of the quality and quantity of returns [18][19][20][21].…”
mentioning
confidence: 99%